Administrative creativity in problem solving and its relationship to job satisfaction among principals of post basic education schools in the North Al-Batinah governorate in the Sultanate of Oman = الإبداع الإداري في حل المشكلات وعلاقته بالرضا الوظيفي لدى مديري مدارس التعليم ما بعد الأساسي بمحافظة شمال الباطنة في سلطنة عمان - Albousaidi, Abdullah Saidabdullah; Ibrahim, Mohd Burhan; Ahmed Mohamed, Ismaiel Hassanein (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study aims to identify administrative creativity and its strategies’ role in solving problems and determining its relationship to job satisfaction among principals of North Al Batinah governorate schools in the Sultanate of Oman. The problem lies in confirming studies that school principals lack the desire and educational experience, which hinders their ability to lead change and the weak elements of creativity and experience in their schools. The researcher adopted the descriptive approach in his study, through a (52) statements questionnaire, distributed in (3) axes are: problems, administrative creativity and job satisfaction. The study population included (141) principals, and a random sample of (39) principals was chosen. The data were analyzed by descriptive analysis method, and Pearson Correlation Coefficient. The study reached several results, including: that there is a positive correlation at the level of significance (0.05) between the level of managers' use of creative methods in solving problems and the level of job satisfaction of employees, also showed a positive correlation at the level of significance (0.05) between the level of managers use of methods Management of organizational conflict and the level of employee satisfaction. ***************************************************************************** تهدف هذه الدراسة الكمية إلى التعرف على الإبداع الإداري واستراتيجياته، ودوره في حل المشكلات وتحديد علاقته بالرضا الوظيفي، لدى مديري مدارس محافظة شمال الباطنة بسلطنة عمان. تكمن المشكلة في تأكيد الدراسات أن مديري المدارس يفتقرون الى الرغبة والخبرة التربوية مما يعيق قدراتهم على قيادة التغير وضعف عناصر الأبداع والخبرة في مدارسهم. اعتمد الباحث المنهج الوصفي في دراسته, بواسطة أداة البحث الرئيسة وهي الاستبيان, حيث تم تصميم استبانة لهذا الغرض, تكونت من ( 52 ) عبارة توزعت في (3) محاور هي: المشكلات والإبداع الإداري والرضا الوظيفي. وقد اشتمل مجتمع الدراسة على (141) مديراً, تم اختيار عينة عشوائية قدرها (39) مديرا. تم تحليل البيانات من خلال منهج التحليل الوصفي، ومعامل ارتباط بيرسون. وقد توصلت الدراسة إلى نتائج عدة منها: أن هناك علاقة ارتباطية موجبة عند مستوى دلالة (0.05) بين مستوى استخدام المدراء لأساليب إبداعية في حل المشكلات ومستوى الرضا الوظيفي للموظفين، كما بينت وجود علاقة ارتباطية موجبة عند مستوى دلالة (0.05) بين مستوى استخدام المدراء لأساليب إدارة الصراع التنظيمي ومستوى الرضا الوظيفي للموظفين.